Development of Project Based Learning Media Using Google Sites on Alternative Energy Topics - Tazkia Dick Laluna; Supurwoko Supurwoko; Shofi Hikmatuz Zahroh (Jurnal Materi dan Pembelajaran Fisika, 2024)
Learning is carried out to arrange and organize the environment around students to foster their learning process. The student's learning process is carried out through inquiry, responding to questions regarding a problem or a complex challenge. This learning process can be conducted by applying the project-based learning model. The project-based learning model can be applied in the field of information and communication technology in line with the 21st century, such as using Google Sites. Therefore, this research aims to describe the specifications of Google Sites as a learning media using the project-based learning model on alternative energy topics and describe the assessment results from experts, educational practitioners, and learners regarding Google Sites as a learning media using the project-based learning model on alternative energy materials. This development research employs the 4D model by Thiagarajan, which consists of the following stages: define, design, develop, and disseminate. The learning media obtained validation from two experts and assessment from educational practitioners regarding content, media, and language aspects. The development trial of this media was conducted with phase E students. Data collection techniques included interviews and questionnaires, with data analysis performed qualitatively and quantitatively. The learning media comprises a primary topic, alternative energy, organized based on project-based learning syntax. It consists of three menus: the welcome menu, the main page, and the author's identity. Validation by experts and assessment by educational practitioners indicate that the learning media meets excellent content, media, and language criteria. The development trial results show that the learning media meets excellent criteria at each trial stage.